The Encoding of Binocular Visual Direction and Stereoscopic Depth Perception in Human Vision - Ba, Yalige (2025)
The visual brain determines the depth and direction of objects in space relative to the viewer. This thesis investigates fundamental mechanisms of binocular vision, focusing on the computation of visual direction, depth perception, and neural plasticity in the adult visual system. Through a series of ten psychophysical experiments, it explores how the brain integrates visual inputs from both eyes to form a unified percept. The findings reveal that binocular visual direction is computed as a weighted average of monocular inputs, with a strong reliance on coarse-scale spatial information. Two competing models of how visual direction is computed were tested, resulting in one account being rejected. Then the variability in egocentric localization across a large sample of individuals was determined. Our data confirm that the visual egocentre is typically located near the median plane of the head, though significant individual differences exist due to the dynamic integration of monocular and binocular cues. When the egocentre is displaced towards one eye, short-term monocular deprivation induces transient shifts in the egocentre location back towards the median plane of the head. This study highlights that egocentre location remains plastic, even in the adult visual system. Finally, we introduce a novel method using linear polarizing filters to quantify eye dominance and assess plastic changes induced by visual deprivation. This method precisely quantifies eye dominance and its plasticity in response to sensory disruption. These findings have important implications for understanding binocular vision as a dynamic and adaptable system, with potential applications for treating visual disorders such as amblyopia and for developing personalized approaches to vision therapy.